The Improvement of Social Care Character Through Puzzle Cards Game - Nugraeny, Annisa Nur; Mukminin, Amirul (Jurusan PGPAUD FIP UNNES, 2019)
Social caring value is one of the values in character that is very important to teach to children. The problem in this study is the decreasing level of concern for others, and less responsiveness when someone needs help. This study aims to determine whether there is an influence in increasing the value of socially caring characters through puzzle card games. The actions or treatments carried out by the researcher are 11 treatments with a total sample of 32 children aged 5-6 years. In this study, the researcher uses a quantitative research approach and the method Is the experimental method. The application of this puzzle card game begins with giving a puzzle card and then the next step can be an experiment or you can also directly ask questions with the children. The result of the study is the value of sig 2 tailed is 0,000 <0,05. It means that there are significant differences between the results of the pretest and posttest data. The average increase in character building of social caring value for children aged 5-6 years is 128.84 increased to 151.91, meaning that there is an increase in the average score of 23.07. Based on the results of this study indicate that puzzle card games can improve the character of social care in children aged 5-6 years in RA Al-Islam Mangunsari 02 Semarang, which before being given action has an average of 128.84, increasing to 151.91.